A LINGUOVERTED IMPACTED TOOTH WITH OROCUTANEOUS FISTULA – A RARE CASE REPORT - G, Srikanth; Kamath, Abhay T.; Kudva, Adarsh; Singh, Anupam; Smriti, Komal; Carnelio, Sunitha (Medicine and Pharmacy Reports, 2018)
The orocutaneous fistulous tract of odontogenic origin is often a diagnostic challenge, due to its rare manifestation and absence of dental signs and symptoms. The odontogenic cutaneous fistula is often misdiagnosed as a superficial skin lesion of non-odontogenic origin delaying the treatment. The diagnosis and treatment must be precise and swift to improve the clinical outcome and minimize the complications. This article presents a rare case of odontogenic keratocyst involving a linguoverted impacted third molar presenting as orocutaneous fistula. The patient was initially treated with empirical antibiotic therapy with no resolution of the cutaneous fistula and thickening of the skin around the sinus opening resulting in cosmetic deformity. Once the fistula was attributed to the underlying odontogenic cyst, treatment was done by cyst enucleation along with the extraction of tooth and fistula excision. The purpose of the paper is to emphasize the importance of early and accurate diagnosis and prompt management of the orocutaneous fistula due to the odontogenic origin.